2012
DOI: 10.1074/jbc.m111.293696
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase Is Internalized by Clathrin-coated Pits and Localizes to a Rab27A/B GTPase-regulated Secretory Compartment in Activated Macrophages

Abstract: Background: Subcellular distribution of NADPH oxidase in macrophages is unclear. Results: In mature (activated) macrophages, NADPH oxidase is contained in a storage compartment and is internalized by clathrin-coated pits. Conclusion: NADPH oxidase trafficking is regulated by external factors. Significance: Subcellular localization of NADPH oxidase relates to pathogen eradication, nature, and severity of oxidative tissue stress as well as redox signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 59 publications
1
37
1
Order By: Relevance
“…This is in disagreement with results seen in DCs, in which Rab27a plays a role in phagosomal maturation, NADPH oxidase delivery to the phagosome, and antigen presentation [84]. In neutrophils or macrophages, participation of Rab27a in phagocytosis was only observed during engulfment of IgGopsonized red blood cells [82,85] but not IgG-opsonized zymosan, which not only engages Fc␥Rs but also binds and signals through mannose receptors and CR3 [85] or serum-opsonized live bacteria [36,82], suggesting that Rab27a is not essential for phagocytosis in neutrophils and macrophages under conditions of systemic infection that involve complex opsonization. Importantly, we demonstrated that different from Rab27a, Munc13-4 is essential for phagosomal maturation during engulfment of serum-opsonized bacteria in neutrophils [36].…”
Section: Regulation Of Neutrophil-specific Functions By Rab27a Gtpasecontrasting
confidence: 54%
“…This is in disagreement with results seen in DCs, in which Rab27a plays a role in phagosomal maturation, NADPH oxidase delivery to the phagosome, and antigen presentation [84]. In neutrophils or macrophages, participation of Rab27a in phagocytosis was only observed during engulfment of IgGopsonized red blood cells [82,85] but not IgG-opsonized zymosan, which not only engages Fc␥Rs but also binds and signals through mannose receptors and CR3 [85] or serum-opsonized live bacteria [36,82], suggesting that Rab27a is not essential for phagocytosis in neutrophils and macrophages under conditions of systemic infection that involve complex opsonization. Importantly, we demonstrated that different from Rab27a, Munc13-4 is essential for phagosomal maturation during engulfment of serum-opsonized bacteria in neutrophils [36].…”
Section: Regulation Of Neutrophil-specific Functions By Rab27a Gtpasecontrasting
confidence: 54%
“…Indeed, the Rab7 adaptor Mon1 is known to displace Rabex-5 from the phagosome, 58 and our results indicate that Rab17 sampling of the efferosome temporally overlaps with Rab7 recruitment to the efferosome. Another Rab GTPase, Rab27, can be localized to the phagosome, 59 activate Rab17 41 and drive exocytosis, 60, 61 indicating that it may be a candidate for the recruitment of Rab17 to the efferosome. However, we were unable to identify Rab27 on efferosomes in either our mass spectrometry screen or by immunofluorescence (data not shown), although the sensitivity and temporal limitations of these methods may have prevented identification of transient or weak Rab27 recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Bone resorption is a complex process combining secretion of protons by the vacuolar H+-ATPase and various lysosomal enzymes, and endocytosis/transcytosis of the degraded products via vesicle transport from apical to basolateral membrane29. Previous studies with various leukocytes have shown that Rab27A is involved in both exocytosis/secretion and endocytosis/phagocytosis303132. Rab27A-deficient neutrophils3334, eosinophils35, basophils36 all show impaired exocytosis.…”
Section: Discussionmentioning
confidence: 99%